Design and Fabrication of a Canvas Belt Thresher for Efficient Cowpea Threshing - Adanu, E. O.; Iya, S. A.; Yakubu, I. T.; Kabri, H. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The increasing demand for efficient and cost-effective cowpea threshing machinery led to the development of a canvas belt thresher. This study focuses on the design and fabrication of a thresher that minimizes grain damage while enhancing threshing efficiency. The machine was constructed using mild steel iron, 22-gauge sheet metal, and canvas materials, ensuring robustness and cost-effectiveness. The total production cost of the machine was ₦253,000, making it affordable for small-scale farmers. The canvas belt system, selected for its rubbing action, was designed to improve grain separation and reduce kernel bruising compared to traditional impact-based mechanisms. Key design considerations included material selection, power transmission, shaft design, and motor capacity to ensure durability, ease of use, and affordability. A 3.18kW gasoline engine powered the thresher, enabling both field and off-field operations. Performance results showed that the machine (1500mm × 800mm × 820mm) operates between 400 to 1200 rpm of drum speed, yielding a high level of efficiency with minimal grain loss and damage. This machine offers a reliable solution for small-scale farmers, significantly reducing labor, time, and operational costs associated with cowpea threshing.